Development of course modules on play and games based on the results of PIAUD students’ laboratory work - Salsabila, Naisa Assyfa (Maliki Interdisciplinary Journal, 2026)
The Play and Games course is a crucial part of the Early Childhood Islamic Education (PIAUD) department, it has an important task in equipping prospective PAUD teachers. This course not only focuses on the theory of play, but also requires students to be able to create, carry out, and evaluate play activities that are educational, creative, and suitable for young children’s ages. Unfortunately, the reality on campus shows that the teaching materials used are still mostly theoretical and do not really accommodate students’ practical experience as a real learning resource. This research aims to create a Play and Games module based on the results of PIAUD students’ practicum. This research uses research and development (R&D) methods with the ADDIE model which includes analysis, design, development, implementation and assessment. The respondents of this research were PIAUD students and lecturers who taught the course. How to collect data using observation, interviews, questionnaires, and document review. The research results show that the modules created are very good according to validation from material and media experts. In addition, this module has proven effective in increasing students’ understanding of concepts, skills in creating educational play events, and students’ ability to reflect on their teaching practices. This module also triggers more lively, contextualized and meaningful learning. Therefore, a module that refers to the results of this practicum is recommended as new teaching material for the Play and Games course in the PIAUD department.